2017
DOI: 10.1186/s12917-017-1022-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D is associated with negative outcome in dogs with protein losing enteropathy: a retrospective study of 43 cases

Abstract: BackgroundHypovitaminosis D has previously been shown to be prevalent amongst dogs with protein losing enteropathy (PLE).The hypothesis of this study was that Low 25-hydroxyvitamin D (25(OH) D) serum concentrations could be a risk factor for negative outcome in dogs with PLE.Forty-three dogs diagnosed with PLE (2005–2014) and which serum Vitamin D serum concentrations were collected and archived at −80 Degrees C were analyzed.Post-diagnostic communication with referring veterinarians was made to determine outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 21 publications
(33 reference statements)
1
92
2
2
Order By: Relevance
“…Several recent studies have reported serum 25‐OH‐D concentration in dogs with specific diseases . Low serum 25‐OH‐D concentrations have been detected in dogs with inflammatory bowel disease and chronic enteropathies, and low vitamin D status has been shown to be an outcome predictor in these patients . Similarly, in dogs with heart disease, a significant association between serum 25‐OH‐D concentration and time to clinical manifestation of congestive heart failure or sudden death was demonstrated ( P = 0.02) .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several recent studies have reported serum 25‐OH‐D concentration in dogs with specific diseases . Low serum 25‐OH‐D concentrations have been detected in dogs with inflammatory bowel disease and chronic enteropathies, and low vitamin D status has been shown to be an outcome predictor in these patients . Similarly, in dogs with heart disease, a significant association between serum 25‐OH‐D concentration and time to clinical manifestation of congestive heart failure or sudden death was demonstrated ( P = 0.02) .…”
Section: Discussionmentioning
confidence: 96%
“…To the authors’ knowledge, the current study is the first to document serum 25‐OH‐D concentrations in critically ill dogs at the time of ICU admission. Several recent studies have reported serum 25‐OH‐D concentration in dogs with specific diseases . Low serum 25‐OH‐D concentrations have been detected in dogs with inflammatory bowel disease and chronic enteropathies, and low vitamin D status has been shown to be an outcome predictor in these patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the FR‐PLE group had significantly lower CIBDAI and CCECAI scores than those found in the IR/NR‐PLE group, the longer survival time of the FR‐PLE group may be attributed to the severity of the disease, which has been shown to be associated with prognosis in dogs with PLE . In addition, other factors, such as body weight, BUN, ALB, and PARR could be associated with survival time . Therefore, further study is needed to evaluate the effect of ULFD itself on the prognosis of dogs with PLE.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship of vitamin D and diseases has also been investigated in dogs and cats, and some studies found association between low vitamin D status and some types of cancer (Selting, Sharp, Ringold, Thamm, & Backus, 2016;Wakshlag et al, 2011;Weidner et al, 2017), congestive heart failure (Kraus et al, 2014;Osuga et al, 2015), gastrointestinal diseases (Allenspach, Rizzo, Jergens, & Chang, 2017;Gow et al, 2011;Lalor et al, 2014;Titmarsh, Gow, Kilpatrick, Cartwright, et al, 2015;Titmarsh, Gow, Kilpatrick, Sinclair, et al, 2015), acute pancreatitis (Kim et al, 2017), acute polyradiculoneuritis (Laws, Kathrani, Harcourt-Brown, Granger, & Rose, 2018), chronic kidney disease (Cortadellas, Fernandez del Palacio, Talavera, & Bayón, 2010;Galler et al, 2012;Gerber, Hässig, & Reusch, 2003 infectious diseases (Lalor et al, 2012;Rodriguez-Cortes et al, 2017;Rosa, Schoeman, Berry, Mellanby, & Dvir, 2013;. Although these studies do not prove a cause-effect relationship, they provide a basis for future studies to investigate possible positive effects of vitamin D supplementation on improving health status and reducing the risk of developing diseases.…”
Section: Introductionmentioning
confidence: 99%